Amorphous MnO2 as Cathode Material for Sodium‐ion Batteries. Issue 8 (15th June 2017) - Zhou, Yirong; Chen, Tong; Zhang, Junxi; Liu, Yao; Ren, Ping
Abstract : Amorphous MnO2 has been prepared from the reduction of KMnO4 in ethanol media by a facile one‐step wet chemical route at room temperature. The electrochemical properties of amorphous MnO2 as cathode material in sodium‐ion batteries (SIBs) are studied by galvanostatic charge/discharge testing. And the structure and morphologies of amorphous MnO2 are investigated by X‐ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and Raman spectra. The results reveal that as‐synthesized amorphous MnO2 electrode material exhibits a spherical morphology with a diameter between 20 and 60 nm. The first specific discharge capacity of the amorphous MnO2 electrode is 123.2 mAhg −1 and remains 136.8 mAhg −1 after 100 cycles at the current rate of 0.1 C. The specific discharge capacity of amorphous MnO2 is maintained at 139.2, 120.4, 89, 68 and 47 mAhg −1 at the current rate of 0.1 C, 0.2 C, 0.5 C, 1 C and 2 C, respectively. The results indicate that amorphous MnO2 has great potential as a promising cathode material for SIBs. Abstract : Amorphous MnO2 has been prepared from the reduction of KMnO4 in ethanol media by a facile one‐pot wet chemical route at room temperature. When employed as cathode material in SIBs, the amorphous MnO2 electrode exhibits high reversible specific capacity, stable cycling performance and good rate capability. The reversible discharge capacity of the amorphous MnO2 electrode is maintained at 136.8 mAhg −1 after 100 cycles at 0.1 C. And the electrode delivers reversible discharge capacities of 120.4, 89, 68 and 47 mAhg −1 at 0.2 C, 0.5 C, 1 C and 2 C, respectively.